Analisis Perlakuan Akuntansi Asset Biologis Berdasarkan PSAK 69 Pada Organisasi Simantri Kelompok Tani Ternak Sapi “Sato Amerta Utama” - I Kadek Agus Setya Mahendra; I Putu Gede Diatmika (Vokasi : Jurnal Riset Akuntansi, 2020)
Biological assets are assets in the form of animals or plants undergoing transformation, resulting in qualitative and quantitative changes. The application of biological assets to date has not been widely used by entities engaged in livestock entities, even though the PSAK 69 standard is active in Indonesia on January 1, 2018. This research was conducted to determine the accounting treatment of biological assets in the Simantri organization Sato Amerta Utama cattle group , Baluk Village based on PSAK 69. The purpose of this study was to determine the measurement, recognition and disclosure of biological assets in Simantri Sato Amerta. This research was conducted using qualitative methods. Data obtained from interviews, observations and documentation. Furthermore, the data from these results are analyzed by data reduction, data presentation and conclusion drawing.This research aims to understand the accounting treatment of biological assets based on PSAK 69 in the Simantri organization of the Sato Amerta Utama cattle group in Baluk Village based on PSAK 69. In this study, to get the data validity is done by triangulation. Achievements in this research show that related to the measurement, recognition and disclosure of biological assets in Simantri Sato Amerta Utama is not fully in accordance with applicable standards, namely PSAK 69. See from the measurement still uses historical costs as acquisition prices and recording is still simple.